Relationship between foot and ankle tendinopathies and dyslipidemia: a literature review - Pedro Luís Ortelani Valadares; Maria Amália Garcia da Silveira Araújo; Isadora Maria de Souza e Silva; Caroline Magrini Turini; Anna Luiza de Araújo Ribeir; Anna Cláudia Ferreira Nunes; ELI ÁVILA SOUZA JÚNIOR (Journal of the Foot & Ankle, 2024)
Objectives: Dyslipidemia is a multifactorial condition related to genetic factors, dietary patterns, sedentary habits, and socioeconomic conditions. Foot and ankle tendinopathies are a common problem in orthopedic consultations and can represent up to 30%, highlighting some risk factors, such as metabolic disorders. Methods: This study is an integrative review of the literature addressing the correlation between foot and ankle tendinopathy and dyslipidemia. The keywords used were: “tendinopathy,” “foot and ankle,” and “dyslipidemia,” with the operators “AND” and “OR” for the search. The following inclusion criteria were established: case reports, cohort studies, case and control studies, clinical trials, and biomechanical studies published between 2013 and 2024, indexed in the following databases: Pubmed (Medline), Scielo, Lilacs, and Scopus, published in English, Spanish, and Portuguese. Results: Several mechanisms have been proposed to explain the correlation between tendinopathies and dyslipidemia, although there is still no absolute clarity; it was shown that the Achilles tendon is the main tendon affected in the foot and ankle, especially by xanthomas, which lead to an increase in the area size, causing pain, edema, difficulty in movement and changes in gait. Conclusion: It is believed that females with dyslipidemia, elderly patients, and individuals with a body mass index below 18.5kg/m2 are more prone to tendinopathies. Level of evidence II; Diagnostic studies.